P27 Changes in cognitive function with the menopausal transition: a longitudinal study in ALSPAC women. (3rd September 2019) - Kilpi, F; Soares, ALG; Fraser, A; Fallon, SJ; Nelson, S; Sattar, N; Tilling, K; Lawlor, DA
Abstract : Background: Prior research has suggested that transient changes or an accelerated decline in cognitive function occur in women going through the menopause transition. The current evidence remains unclear as to whether these changes occur over and above those of general ageing and the extent to which they are influenced by learning from repeating the cognitive tests. The aims of this study were to (i) assess change in cognitive function by increasing reproductive age in women in mid-life, and (ii) examine the association of change in reproductive hormone levels with change in cognitive function in these women. Methods: The data were obtained from the follow-up of mothers of the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort, UK. There were up to three repeat measurements of six cognitive function tests in 2, 411 women (at mean ages 51, 52 and 53). The six tests covered different domains of cognitive function: processing speed, working memory, verbal episodic memory, verbal intelligence and verbal fluency. We analysed how cognitive function in different domains changed with years since final menstrual period (reproductive age) while controlling for chronological age, learning effects and socioeconomic factors using multilevel regression models. We also assessed the association of changes in reproductive hormones (luteinizing, follicle-stimulating and anti-Mullerian hormones) with changes in cognitive test performance. Results: With one exception there was little evidence of any of the cognitive function domains changing in relation to reproductive age, but processing speed showed a decline by -0.21 (95% CI -0.34; -0.08) standard deviations (SD) per 10 years since final menstrual period. Change in reproductive hormones were not robustly associated with processing speed and other measures of cognitive function, with the exception of immediate verbal episodic memory, with both increasing follicle-stimulating and luteinizing hormone levels being associated with a decline in this domain (-0.06 (95% CI -0.09; -0.02) and -0.06 (95% CI -0.10; -0.02) SD change, respectively). Discussion: We found little evidence for reproductive age or change in reproductive hormones having an important effect on women's cognitive function in mid-life. Of the 24 associations estimated, there was evidence of decline in two of the six cognitive domains, but these were not consistent between reproductive age and reproductive hormones.